Lethal Consequences of Overcoming Metabolic Restrictions Imposed on a Cooperative Bacterial Population - Eunhye Goo (American Society for Microbiology, 2017)
ABSTRACT Quorum sensing (QS) controls cooperative activities in many Proteobacteria. In some species, QS-dependent specific metabolism contributes to the stability of the cooperation. However, the mechanism by which QS and metabolic networks have coevolved to support stable public good cooperation and maintenance of the cooperative group remains unknown. Here we explored the underlying mechanisms of QS-controlled central metabolism in the evolutionary aspects of cooperation. In Burkholderia glumae, the QS-dependent glyoxylate cycle plays an important role in cooperativity. A bifunctional QS-dependent transcriptional regulator, QsmR, rewired central metabolism to utilize the glyoxylate cycle rather than the tricarboxylic acid cycle. Defects in the glyoxylate cycle caused metabolic imbalance and triggered high expression of the stress-responsive chaperonin GroEL. High-level expression of GroEL in glyoxylate cycle mutants interfered with the biosynthesis of a public resource, oxalate, by physically interrupting the oxalate biosynthetic enzyme ObcA. Under such destabilized cooperativity conditions, spontaneous mutations in the qsmR gene in glyoxylate cycle mutants occurred to relieve metabolic stresses, but these mutants lost QsmR-mediated pleiotropy. Overcoming the metabolic restrictions imposed on the population of cooperators among glyoxylate cycle mutants resulted in the occurrence and selection of spontaneous qsmR mutants despite the loss of other important functions. These results provide insight into how QS bacteria have evolved to maintain stable cooperation via QS-mediated metabolic coordination. IMPORTANCE We address how quorum sensing (QS) has coevolved with metabolic networks to maintain bacterial sociality. We found that QS-mediated metabolic rewiring is critical for sustainable bacterial cooperation in Burkholderia glumae. The loss of the glyoxylate cycle triggered the expression of the stress-responsive molecular chaperonin GroEL. Excessive biosynthesis of GroEL physically hampered biosynthesis of a public good, oxalate. This is one good example of how molecular chaperones play critical roles in bacterial cooperation. In addition, we showed that metabolic restrictions in the glyoxylate cycle acted as a selection pressure on metabolic networks; there were spontaneous mutations in the qsmR gene to relieve such stresses. However, the presence of spontaneous qsmR mutants had tragic consequences for a cooperative population of B. glumae due to failure of qsmR-dependent activation of public good biosynthesis. These results provide a good example of a bacterial strategy for robust cooperation via QS-mediated metabolic rewiring.